Synergistic effects of Bi-metal oxide–graphene oxide nanocomposites in photodegradation applications - Govindarajalu Kishore; Periyasamy Pritha; S. Xavier; D. Bhakiaraj; Francisxavier Paularokiadoss; Christian A. Celaya; Mohammad Mansoob Khan (Next Nanotechnology, 2025)
The present study focuses on synthesizing two graphene-based composites, GO/CaO and GO/BaO, for photodegradation applications towards the methylene blue dye. The polycrystalline nature of the composites was determined by the XRD analysis with an average crystalline size of 14.9 nm. Raman analysis and FT-IR spectral analysis were used to determine the interaction between GO and the metal oxides. The optical band gap was evaluated to be 3.2 eV and 4.2 eV, with an absorbance λmax of around 242 nm. The PL analysis confirms the electron mobility within the composites with an emission peak of 694 nm. The elemental composition and chemical state of the composites were evaluated using XPS analysis, providing valid results for the C1s peak at 284 eV, which corresponds to the C-C and CC bonds. The photocatalytic degradation of the dye molecule was investigated by utilizing natural sunlight as the irradiation source to assess the practical applicability of the synthesized composites. The maximum degradation percentage achieved by the GO/CaO was 90 % with a period of 120 min under natural sunlight, showing a promising catalyst with a cost-effective and environmentally friendly composite for real-world wastewater treatment.